2016
DOI: 10.1136/jnnp-2016-313660
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitors are associated with weight loss in older people with dementia: a systematic review and meta-analysis

Abstract: We conducted a systematic review and meta-analysis investigating the influence of acetylcholinesterase inhibitors (AChEIs) therapy on nutritional status and weight across observational and interventional studies. Two authors searched major electronic databases from inception until 10/14/2015 for longitudinal, open-label and randomised double-blind placebo controlled (randomised controlled trials (RCTs)) studies of AChEIs in patients with dementia reporting nutritional status outcome data. Out of 3551 initial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
(31 reference statements)
1
26
0
1
Order By: Relevance
“…First, polypharmacy may contribute to the development of frailty through a negative influence on factors associated with frailty (such as comorbidities) or factors included in frailty definitions such as weight loss. 26,27 Further, polypharmacy has been linked to inappropriate prescribing, 28 low adherence, 29 preventable and unplanned hospitalization, 30 and adverse drug events, 31 all relevant to the development of frailty. This is particularly relevant to older individuals, who are more susceptible to adverse drug reactions, 32 also caused by commonly used medications.…”
Section: Discussionmentioning
confidence: 99%
“…First, polypharmacy may contribute to the development of frailty through a negative influence on factors associated with frailty (such as comorbidities) or factors included in frailty definitions such as weight loss. 26,27 Further, polypharmacy has been linked to inappropriate prescribing, 28 low adherence, 29 preventable and unplanned hospitalization, 30 and adverse drug events, 31 all relevant to the development of frailty. This is particularly relevant to older individuals, who are more susceptible to adverse drug reactions, 32 also caused by commonly used medications.…”
Section: Discussionmentioning
confidence: 99%
“…Soysal et al [77] concluded that acetylcholinesterase inhibitors could cause weight loss and change muscle mass index in elderly people. Despite not showing a direct relation with BFT, it is clear that this gene has a role during animal’s muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Additionally, they have serious adverse effects (eg sedation, postural hypotension, metabolic syndrome issues and electrolyte changes, drug interactions, cardiac arrhythmia, extrapyramidal symptoms, and falls). [10][11][12][13] Because of the complications associated with the pharmacological treatment, current guidelines recommend that nonpharmacological interventions should be attempted first, followed by the least harmful medication for the shortest time possible time. 14 Therefore, new interventions, added to drug therapy, are considered a potential alternative treatment to reduce or prevent NPs onset and recurrence.…”
mentioning
confidence: 99%